A methodology for filtering point cloud generated by CMM to apply NURBS. Issue 6 (2nd November 2018) - Oh, Ji W.; Park, Sang C.
ABSTRACT: Nowadays, as aeronautical technology develops, an output of turbine is increasing. A BLISK is a single engine component consisting of a rotor disk and blades, which may be either integrally cast, machined from a solid piece of material, or made by welding individual blades to the rotor disk. Although there have been many previous researches, they didn't study related to measurement. A BLISK must be measured since it is critical components related to safety. A 5-axis CMM is used in product measurement system. The 5-axis CMM is suitable for measuring complex shapes because the surface is measured using a probe in contact with the object. 5-axis CMM moves the probe in contact with the surface of the workpiece, leaving a trace of points continuously. However, it is difficult to obtain the desired mesh with the existing algorithm using the data. So this paper proposes that a methodology for filtering point cloud generated by 5-axis CMM to apply NURBS. GRAPHICAL ABSTRACT: